ANALISIS INTERNALISASI SIKAP PROFIL LULUSAN MAHASISWA PGMI BERBASIS LEVEL AFEKTIF - Muthia Afifah; Nida Murwandini; Dita Ayu Nur Afrilia; Alina Halda Nur (STKIP Subang, 2026)
Affective domain self-assessment is frequently challenged by subjectivity and overestimation biases, often leading to excessively positive outcomes among students. This study aims to evaluate the affective attitude profile of Islamic elementary school teacher candidates based on Krathwohl’s affective taxonomy levels, focusing on the achievement of graduate profile dimensions. A descriptive quantitative method was employed through a survey involving 32 fourth-semester students of the Primary School Teacher Education (PGMI) program at UIN Syarif Hidayatullah Jakarta. Data were collected using a self-assessment instrument consisting of a 40-item questionnaire that measures eight graduate profile dimensions across five distinct affective levels. The data analysis revealed that the collective attitude quality of the students falls into an exceptionally high category. Specifically, 29 students (90.6%) achieved the